Incorporating principles of instructional leadership in love pedagogy towards school excellence: teachers perspectives - Salleh, Mohamad Johdi; Mitul, Sharmin Jahan (Asian Scholars Network, 2021)
This study seeks to examine school principals’ practice of incorporating instructional leadership principles in love pedagogy towards achieving school excellence from teachers’ perspectives. Love pedagogy is an approach to fuse sharing, caring, affection, wisdom, and, passion in achieving noble visions and missions of an organization or institution. The Principal Instructional Management Rating Scale (PIMRS) on development; formulated, modified and adapted by Hallinger and Murphy (1985), Latip (2006), Hatta (2011) and McCarley, Peters, & Decman (2016) was used as the instrument for data collection specifically its survey questionnaire. The respondents were 328 educational leaders and teachers from various states in Malaysia. They were pursuing degree in Master of Education at the Kulliyyah of Education in IIUM. The findings of this study indicated that the leading practice of principals when incorporating instructional leadership principle towards school excellence was ‘Passionate in Developing Academic Standard’ with a mean of 5.1445 agreeing to this practice. This was then followed by ‘Sharing in Communicating School Goals’ achieved a mean of 5.1366 and ‘Caring in Supervising and Evaluating Instructions’ had a significant mean of 5.0073 agreed to the practice. This research hopes to provide useful discoveries to effectively assist school principals, educational leaders and teachers to improve performance of schools in order to achieve first class human capital who are excellent nationally and internationally as stipulated in the vision and mission of excellence school by the Ministry of Education Malaysia towards realization of the Malaysian Education Blueprint 2013-2025 and the Malaysia Development Plan 2030.